2011
DOI: 10.2174/156802611798808460
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Transferring Regions of gp41 as Targets for HIV-1 Fusion Inhibition and Viral Neutralization

Abstract: Abstract:The fusogenic function of HIV-1 gp41 transmembrane Env subunit relies on two different kinds of structural elements: i) a collapsible ectodomain structure (the hairpin or six-helix bundle) that opens and closes, and ii) two membrane-transferring regions (MTRs), the fusion peptide (FP) and the membrane-proximal external region (MPER), which ensure coupling of hairpin closure to apposition and fusion of cell and viral membranes. The isolation of naturally produced short peptides and neutralizing IgG-s, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 118 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…Thus, they used leakage of aqueous contents induced by the synthetic HIV-FP as a surrogate assay for self-oligomerization in membranes. Subsequently, a D-hexapeptide library was screened for its capacity to block FP-induced leakage (for a description of this assay see also (Huarte et al, 2011)). Using this approach two hexapeptides were identified that blocked gp41-induced fusion, thereby supporting the FP region as a potential target for inhibitor development.…”
Section: Prospects As Therapeutic Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, they used leakage of aqueous contents induced by the synthetic HIV-FP as a surrogate assay for self-oligomerization in membranes. Subsequently, a D-hexapeptide library was screened for its capacity to block FP-induced leakage (for a description of this assay see also (Huarte et al, 2011)). Using this approach two hexapeptides were identified that blocked gp41-induced fusion, thereby supporting the FP region as a potential target for inhibitor development.…”
Section: Prospects As Therapeutic Targetsmentioning
confidence: 99%
“…Thus, the themes of glycoprotein structure-function common to all enveloped viruses are highly significant for the understanding of the general mechanism of protein-mediated fusion Chernomordik and Kozlov, 2003;Cohen and Melikyan, 2004;Harrison, 2008;Hernandez et al, 1996;Kozlov et al, 2010;Lentz et al, 2000;Melikyan, 2008). In addition, the conserved elements of these machineries, transiently or permanently exposed on the virion surface, provide clinical targets for development of inhibitors (antivirals) and immunogens (vaccines) (Blumenthal and Dimitrov, 2007;Doms and Moore, 2000;Eckert and Kim, 2001;Forssmann et al, 2010;Huarte et al, 2011;Munch et al, 2007). Fig.…”
Section: Introduction: Viral Glycoprotein-induced Membrane Fusionmentioning
confidence: 99%
“…To investigate factors influencing the P16‐mediated enhancement of viral infection, we analyzed the sequence characteristics of the MPER domain. MPER, a highly conserved and Trp‐rich domain in the gp41 transmembrane envelope subunit of HIV‐1, plays an important role in viral fusion and infectivity and thus is targeted by broadly neutralizing antibodies 4E10, 2F5. and Z13e1 .…”
Section: Introductionmentioning
confidence: 99%